A new group of species of the genus Megalothorax (Collembola, Neelidae) with Gondwanan distribution, and introducing an open interactive identification key of Megalothorax species - Schneider, Clément; Minor, Maria A.; D’haese, Cyrille A. (Zootaxa, 2023)
Megalothorax Willem, 1900 is a genus of Neelidae (Collembola) with worldwide distribution. Three new species are described here: Megalothorax anterolenis sp. nov. (Patagonia, Chile), Megalothorax tasmanterolenis sp. nov. (Tasmania, Australia) and Megalothorax zealanterolenis sp. nov. (the South Island, New Zealand). New descriptive elements are also provided for Megalothorax rubidus. Two of the new species were sequenced (COI, 16S rDNA, 28S rDNA). Within the genus, the three new species form a new group of species characterised by the absence of secondary granulation dorsally on the head and the thorax, a reduced chaetotaxy of the basomedian field of labium, a bifurcate hair on the maxillary outer lobe and an enlarged S-chaeta (Sa2) on Ant. IV. The molecular based phylogeny further supports the sistership of the two sequenced species. The possible Gondwanan origin of the new group is discussed. Elements of discussion are also provided regarding the possible function of the incomplete coverage of secondary granulation. Finally, an open interactive identification key for the Megalothorax species of the world is introduced.